2019
DOI: 10.1016/j.devcel.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Progression through a Continuum of Transit-Amplifying Progenitor Cell States Regulates Blood Cell Production

Abstract: Graphical Abstract Highlights d Transcriptomic continuums correlate with phenotypic continuums in erythropoiesis d Degree of developmental progression per cell cycle governs proliferative capacity d Glucocorticoids uncouple cell division and differentiation speed in erythropoiesis d Erythroid progenitor cell divisions are symmetric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Indeed, it has been known for decades that erythroid progenitors give rise to colonies of different sizes and morphology in the methylcellulose culture system, which led to the concept of large, intermediate, and small BFU-E colonies, with the small BFU-E-forming cells further differentiating into CFU-Es (46). The recent progress of single-cell technologies has enabled stringent analyses of these varied cell populations with regard to both steroid sensitivity and cell-fate decisions (12,47). Although we previously found that human BFU-Es and CFU-Es can be immunophenotypically defined on the basis of IL-3R, GPA, CD34, and CD36 cell-surface markers, this characterization did not allow us to fully resolve the heterogeneity of human erythroid progenitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been known for decades that erythroid progenitors give rise to colonies of different sizes and morphology in the methylcellulose culture system, which led to the concept of large, intermediate, and small BFU-E colonies, with the small BFU-E-forming cells further differentiating into CFU-Es (46). The recent progress of single-cell technologies has enabled stringent analyses of these varied cell populations with regard to both steroid sensitivity and cell-fate decisions (12,47). Although we previously found that human BFU-Es and CFU-Es can be immunophenotypically defined on the basis of IL-3R, GPA, CD34, and CD36 cell-surface markers, this characterization did not allow us to fully resolve the heterogeneity of human erythroid progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the specific mechanisms of action of glucocorticoids in the erythroid system in both healthy individuals and patients with DBA remain to be fully elucidated. Several studies have demonstrated that glucocorticoids act at the erythroid progenitor level, but the precise stages of erythroid differentiation at which they exert their effects have not been identified (10)(11)(12)(13). This is due in part to the considerable heterogeneity of erythroid progenitor populations and the different markers and model sys-Despite the effective clinical use of steroids for the treatment of Diamond Blackfan anemia (DBA), the mechanisms through which glucocorticoids regulate human erythropoiesis remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…30 Further it has been shown that the tight link between the number of cell divisions and differentiation can be uncoupled by treatment with glucocorticoids, thought to be acting on developmental regulatory proteins. 42 How this occurs in the case of CDA-I is not yet clear although previous findings from non-erythroid cell lines show Codanin-1 to be cell cycle regulated 7 and cause an increase in cell cycle rate if over-expressed. 5 The final stages of erythropoiesis involve chromatin and nuclear condensation prior to expulsion of the pyknotic nuclei by enucleation 36,43 and this process is highly organized 44 with chromatin condensation playing an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been known for decades that erythroid progenitors give rise to colonies of different sizes and morphology in the methylcellulose culture system which led to the concept of large, intermediate and small BFU-E colonies and that the small BFU-E forming cells further differentiate into CFU-E (36). The recent advent of single cell technologies has also enabled finer analysis of these varied populations in terms of both steroid sensitivity and cell fate decisions (12,37).…”
Section: Discussionmentioning
confidence: 99%
“…The actions of glucocorticoids have been well studied in many disease contexts, but their specific mechanisms of action in the erythroid system in both healthy individuals and patients with DBA still remains to be fully elucidated. Several studies have demonstrated that glucocorticoids act at the erythroid progenitor level but the precise stages of erythroid differentiation at which they exert their effects is not yet known (10)(11)(12)(13). This is in part due to the significant heterogeneity of erythroid progenitor populations and the different markers and model systems that are used for studying erythropoiesis and the effects of glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%